1981
DOI: 10.1113/jphysiol.1981.sp013618
|View full text |Cite
|
Sign up to set email alerts
|

The effect of (+)‐tubocurarine on neuromuscular transmission during repetitive stimulation in the rat, mouse, and frog.

Abstract: SUMMARY1. The effect of tubocurarine on amplitudes of end-plate currents in response to trains of repetitive stimulation (50-150/sec) was investigated in voltage-clamped muscle fibres of the rat, mouse and frog.2. In rat and mouse muscle, the presence of tubocurarine led to a more rapid decline (rundown) in the amplitudes of successive end-plate currents during trains of impulses. In frog, tubocurarine caused an increase in apparent facilitation of end-plate current amplitudes during the first few impulses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 37 publications
6
46
1
Order By: Relevance
“…Equal concentrations of Phen did not alter the rundown of successively evoked e.p.ps as did tubocurarine (Figure 6). The faster rundown of the endplate current amplitudes recorded in the presence of tubocurarine have been attributed to its prejunctional actions (Glavinovic, 1979b;Magleby et al, 1981;. A faster decay of the e.p.p.…”
Section: Evoked Transmitter Releasementioning
confidence: 99%
“…Equal concentrations of Phen did not alter the rundown of successively evoked e.p.ps as did tubocurarine (Figure 6). The faster rundown of the endplate current amplitudes recorded in the presence of tubocurarine have been attributed to its prejunctional actions (Glavinovic, 1979b;Magleby et al, 1981;. A faster decay of the e.p.p.…”
Section: Evoked Transmitter Releasementioning
confidence: 99%
“…train run-down in tubocurarine, Magleby et al (1981) concluded that the effect was not a consequence of channel block and must therefore be the result of a prejunctional action. To test this hypothesis, the effects of tubocurarine and trimetaphan were examined on trains of e.p.c.s evoked by repetitive (50 Hz) ionophoretic application of short pulses of ACh to the end-plate, and these effects were compared to their effects on trains of neurally evoked e.p.c.s.…”
Section: Effects Of Trimetaphanmentioning
confidence: 99%
“…Controversy has arisen as to whether the action of tubocurarine which leads to run-down of trains of e.p.p.s or e.p.c.s during repetitive stimulation may be prejunctional in origin (Blaber, 1970(Blaber, , 1973Hubbard & Wilson, 1973;Glavinovic, 1979b;Magleby, Pallotta & Terrar, 1981), or whether it represents a use-dependent block of the receptor-associated ion channel (Dreyer, 1982), of the type first suggested for tubocurarine by Manalis (1977) and Katz & Miledi (1978) and later comprehensively studied by Colquhoun, Dreyer & Sheridan (1979).…”
Section: Introductionmentioning
confidence: 99%
“…Others have suggested that the binding site involved in the production of fade could be a presynaptic AChR [2][3][4][5][6][7][8]. In evaluation of our data it is important to underscore the fact that all efforts to detect interaction or binding of o~-toxins to putative presynaptic ACh receptors of any type have been unsuccessful [11].…”
Section: Discussionmentioning
confidence: 99%